1997
DOI: 10.1038/ng1297-423
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenesis and a DNA repair defect in mice with a truncating Brca2 mutation

Abstract: Germline mutation of the BRCA2 gene carries a high risk of developing breast cancer. To study the function of this gene, we generated a mutation in Brca2 in mice. Unlike other mutations in the Brca2 gene, which are lethal early in embryogenesis when homozygous, some of our homozygous mutant mice survive to adulthood. These animals have a wide range of defects, including small size, improper differentiation of tissues, absence of germ cells and the development of lethal thymic lymphomas. Fibroblasts cultured fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
285
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(296 citation statements)
references
References 46 publications
11
285
0
Order By: Relevance
“…Notably, osteosarcoma development in both male and female Brca2 À/À rats occurred at a frequency of 20%, a site not common in the limited surviving mice having terminal deletions of exon 11 (Connor et al, 1997;Friedman et al, 1998). Homozygous deletion of exon 27 in mice resulted in the development of various epithelial carcinomas, lymphomas and sarcomas however, no osteosarcomas and only one ovarian tumor were reported (McAllister et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, osteosarcoma development in both male and female Brca2 À/À rats occurred at a frequency of 20%, a site not common in the limited surviving mice having terminal deletions of exon 11 (Connor et al, 1997;Friedman et al, 1998). Homozygous deletion of exon 27 in mice resulted in the development of various epithelial carcinomas, lymphomas and sarcomas however, no osteosarcomas and only one ovarian tumor were reported (McAllister et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous mice with severe truncations of the Brca2 protein before exon 11 or resulting in the deletion of this exon are embryonic lethal (reviewed by Moynahan, 2002). Homozygous Brca2 knockout mice with some of the BRC repeats in exon 11 left intact are infertile, have a limited life span and develop thymic lymphoma (Connor et al, 1997;Friedman et al, 1998). In contrast, truncation of a small region of the carboxyl end of Brca2 results in fertile animals with no gross abnormalities that are predisposed to cancer (McAllister et al, 2002), although there is B30% reduced viability than expected for homozygous mice.…”
Section: Introductionmentioning
confidence: 99%
“…Germline mutations in the breast-cancer susceptibility gene BRCA2 confer susceptibility to familial early-onset breast and ovarian cancers (Wooster et al, 1994(Wooster et al, , 1995Tavtigian et al, 1996;Brody and Biesecker, 1998;Rahman and Stratton, 1998). Extensive studies have indicated that BRCA2 has an important function in DNA repair (Connor et al, 1997;Mizuta et al, 1997;Sharan et al, 1997;Wong et al, 1997;Chen et al, 1998;Patel et al, 1998). Recent reports indicate that BRCA2 acts in the homology-directed recombinational repair of double-strand DNA breaks (Davies et al, 2001;Moynahan et al, 2001;Xia et al, 2001;Kraakman-van der Zwet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Tumorigenesis in carriers of germ-line mutations in BRCA1 and BRCA2 is invariably accompanied by loss of the wild-type allele (Smith et al, 1992;Neuhausen and Marshall, 1994;Collins et al, 1995;Gudmundsson et al, 1995;Kelsell et al, 1996) suggesting that the proteins encoded by the two genes operate as tumour suppressors. An increasing-body of evidence favours a role for both BRCA1 and BRCA2 in cellular response to DNA damage (Connor et al, 1997;Scully et al, 1997;Patel et al, 1998). It is postulated that the BRCA genes act as caretakers, functioning to maintain genomic stability, rather than as gatekeepers which regulate cellular proliferation (Brugarolas and Jacks, 1997;Kinzler and Vogelstein, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular basis for this is not known. Analysis of ®broblasts derived from mice homozygous for a truncating mutation in BRCA2 has revealed a proliferation defect associated with p53-dependent induction of p21 Waf1 expression, and a DNA repair defect (Connor et al, 1997). In another study, mouse embryo ®broblasts carrying BRCA2 truncations, were shown to be signi®cantly more sensitive to UV irradiation and the alkylating agent methylmethanesulphonate than wild-type controls, leading to the suggestion that BRCA2 may be associated with a nucleotide excision repair pathway (Patel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%